Effect of ecological civilization pilot demonstration area construction on urban land green use efficiency - Li, Shaojie; Wang, Duoduo; Wu, Qin (Frontiers in Environmental Science, 2023)
Improvement of urban land green use efficiency (ULGUE) in the context of sustained economic growth is a major challenge for the regional sustainable development and ecological civilization construction in China. This study measures the ULGUE of 263 cities in China at the prefecture or above level, clarifies its spatio-temporal changes, investigates the effect of ecological civilization pilot demonstration area construction on ULGUE with the multi-period PSM-DID model and spatial Durbin difference model, and evaluates the spatial spillover effect of the policy. The results show that: 1) In terms of spatio-temporal changes, ULGUE shows a steady upward trend with time. From 2006 to 2019, the national mean value of ULGUE increases from 0.5284 to 0.6439, with an increase rate of 21.86%; in the spatial dimension, ULGUE is characterized by a pattern of eastern > national > central > western. 2) Ecological civilization pilot demonstration area construction has significantly improved the ULGUE of pilot cities by about 0.12% relative to that of non-pilot cities, which was validated by the robustness test. 3) Ecological civilization pilot demonstration area construction has significant positive spillover effects on the ULGUE of neighboring cities, which are related to the urban characteristics such as geographical location, resource endowment, and environmental protection intensity. 4) Ecological civilization pilot demonstration area construction has certain heterogeneity in its effect on ULGUE in different regions and cities, with a more significant promoting effect for non-eastern regions, non-resource-based cities, and non-key cities of environmental protection. Therefore, it is necessary to summarize the successful experience of ecological civilization pilot demonstration area construction and fully consider differential policies, so as to maximize the policy dividends while strengthening regional linkage, and further contribute to national popularization of this policy.